2006
DOI: 10.1783/147118906778586598
|View full text |Cite
|
Sign up to set email alerts
|

Delphi method and nominal group technique in family planning and reproductive health research

Abstract: QUALITATIVE RESEARCH But is she positive?Your next patient is pregnant but doesn't want to be.Where next? As a registered charity since 1968, bpas has offered affordable abortion care for women. We provide almost 50,000 abortions a year (including service agreements) and can offer all the professional help your patient needs.bpas has a nationwide network of clinics and consultation centres. There are no long waits for appointments. We can offer a choice of times, clinics and procedures. All it takes to arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 33 publications
0
55
0
1
Order By: Relevance
“…The DT has been used widely in pediatric rheumatology (as discussed in later examples) and other medical specialties [6][7][8].…”
Section: The Delphi Techniquementioning
confidence: 99%
“…The DT has been used widely in pediatric rheumatology (as discussed in later examples) and other medical specialties [6][7][8].…”
Section: The Delphi Techniquementioning
confidence: 99%
“…However, it may be temping for expert facilitators to interject their own opinions, which would bias the findings. The validity (Van Teijlengen et al, 2006) and reliably (Vella et al, 2000) of NGT has been demonstrated. NGT is an effective technique for an exploratory study.…”
Section: Advantages and Limitations Of Ngtmentioning
confidence: 99%
“…As in focus groups, the results of the NGT cannot be generalized to a wider population due to the limited number of participants. Notwithstanding the possibility to test the results of a NGT by using a survey with a representative sample, the initial selection of the NG participants is a key factor and is open to bias due to the specific characteristics of the participants, both in terms of who is selected to attend (a possible selection bias), and who agrees to participate (a potential response bias) (van Teijlingen et al, 2006). In research with professionals aimed at consensus, the level of expertise is crucial to its success and the validity of the data it generates (Harvey & Holmes, 2012).…”
Section: Weaknesses Of Ngtmentioning
confidence: 99%
“…The starting question in itself is a critical and potentially weak element. NGT's discussion stages do not guarantee anonymity, which may limit participants' willingness to express their views, especially on more controversial issues (Fein et al 1997;Van Teijlingen et al 2006). Even structured group processes may be influenced by powerful social dynamics, especially in adolescent populations (Ramirez et al, 2000).…”
Section: Weaknesses Of Ngtmentioning
confidence: 99%